The Infancy Gospel of Thomas - Cielontko, David; Nicklas, Tobias; Bremmer, Jan N. (Studies on early Christian Apocrypha, 2025)
"The Infancy Gospel of Thomas is one of the weirdest and most problematic writings of early Christianity, but despite recent advances in its understanding it still does not receive the attention it deserves. This volume begins with two chapters on introductory issues such as the title, the audience, the transmission, the time and place of the original text, and its Sitz im Leben. The next three chapters focus first on a literary analysis arguing for a partially coherent plot showing the development of Jesus in his childhood, and then on aspects of Jesus’ upbringing and the ways in which different versions reflect readers’ discomfort with Jesus letting other children die. Subsequent chapters consider the material aspects of the textual transmission, including an exciting new papyrus. The volume concludes with three versions of the Infancy Gospel of Thomas that have been very little studied – Georgian, Ukrainian and Old Czech – and are virtually unknown in the Anglophone world. All of these are here translated into English for the first time."